The influence of customer relationship management, service quality and brand image, on customer loyalty of balqis laundry, tegal regency - Fitriyanti, Hanifah; Fauzi, Irsal (International Journal of Applied Finance and Business Studies, 2025)
This study aims to determine and analyze the influence of Customer relationship management, service quality and brand image on customer loyalty. In an effort to obtain the required data, the method used is a Questionnaire. The data analysis technique of this study uses multiple regression analysis. The results of this study indicate that Customer relationship management has a positive effect on customer loyalty, where the better the implementation of customer relationship management, the higher the customer loyalty will be. Service quality has a positive effect on customer loyalty, where the better the service quality provided by employees and owners of Balqis Laundry, the higher the customer loyalty will be. Brand Image has a positive effect on customer loyalty, where the better the brand image owned by Balqis Laundry, the higher the customer loyalty will be